ANALYSIS OF THE BRIGHT FIREBALL OVER TURKEY ON MAY 27, 2020 - Unsalan, O.; Kruglikov, N. A.; Yesilyaprak, C.; Pastuhovich, A. Yu; Altunayar-Unsalan, C.; Goodall, J.; Mickaelian, A. M. (Wiley, 2021)
[Abstract Not Available]
84th Annual Meeting of the Meteoritical-Society -- AUG, 2021 -- Chicago, IL